Determining Water Conservation attributes, their effects on Soil and Plants, Distributions in the Fields of Gharecharian using GIS and RS - Assadian, Farideh; Khalafi, Jafar; Daneshfar, Hassan (International Journal of Bio-resource and Stress Management, 2023)
Studying the quantity and duration of water supply and the degree of its effect on plant cover, in different parts of the distribution field of flood water is of great importance in order to properly manage the water distribution system. Here, the degree of success in using satellite pictures pertaining to the flood water distribution has been well depicted in connection with water supply map. Preparation was examined and the best band or combination of bands produced by processing Aster data was selected. The boundary map of the flood water distribution station in Gharecharian was prepared at first and the position of the constructed installation was drawn using GPS. In field operations, hydrometer station was used to measure the amount of flood water entering into the field. 15 graded rulers for measuring the height of water in distribution canals were positioned and 12 transmission gates were randomly selected to record the height of the water at the time of flood water distribution. Then an aerial field map was prepared according to the water height changes and also quantity of plant cover in different parts of the field. With the use of desired factor variance and correlating factor among pictures and also visual observation, six pictures were selected for the final classification from among the 18 acquired pictures from different groups. Inspection of the degree of precision for the classification was done by confusion matrix. The highest index calculated (83.5) was of Kappa Index for FA1, PC1 and MND which indicated that the mentioned combination have the most Consistent with the ground truth map.